Towards a more effective and reliable salt crystallisation test for porous building materials: Predictive modelling of sodium chloride salt distribution. (18th October 2021) - D'Altri, Antonio Maria; de Miranda, Stefano; Beck, Kevin; De Kock, Tim; Derluyn, Hannelore
Graphical abstract: Highlights: A procedure for accumulating salts at the surface of porous materials is defined. Experimental verification is limited to two porous limestones. A multiphase numerical model reproduces the procedure with NaCl. In silico testing allows to predict the general applicability of the procedure. The procedure holds for different stones, salt concentrations and drying RH. Abstract: The RILEM TC ASC-271 is designing a new procedure to assess the durability of porous building materials to salt crystallisation in the laboratory, consisting of a salt accumulation and a damage propagation phase. The salt accumulation consists of the capillary absorption of a salt solution followed by drying at low humidity to crystallize salts close to the evaporative surface without inducing damage. This was experimentally verified on Maastricht and Migné limestone but poses the question of whether the accumulation procedure can be extrapolated to other porous building materials and if the salt distribution is influenced by the salt concentration and drying conditions. Using a multiphase numerical model, sodium chloride accumulation can be accurately predicted for both stones. Furthermore, numerical simulations confirm that the protocol remains valid for other porous building materials and while moderately varying the concentration of the absorbed salt solution and the relative humidity while drying. Consequently, the protocol's general applicability is confirmed, proving its suitability for developing a more effective salt crystallization test.